Pentingnya Motivasi pada Proses Pembelajaran Siswa di SD-IT Ayadil Ikhwah Kota Mataram, Nusa Tenggara Barat - Shabrina, Nur; Nabila, Faizah; Ulandari Puji Lestari, Sri; Suci Ramadhani, Ninda; Noviyani, Sarifah (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
Motivation is crucial for learning in school. Without motivation, students tend to have low self-confidence. On the other hand, students may lack enthusiasm for learning and fail to achieve their learning goals. The issue in this study is whether the motivation provided by the teacher at Ayadil Ikhwah Elementary School in Mataram has been implemented effectively or not. The subjects of the study are the teachers and students of Grade 1 at SD-IT Ayadil Ikhwah. The research method employed is qualitative descriptive. Data collection was conducted through interviews, observations, and documentation. Data were analyzed using critical analysis with the model by Miles and Huberman. Based on the research findings, the motivation provided to the students of Grade 1 at SD-IT Ayadil Ikhwah is still categorized as low. This is evidenced by many students still showing a lack of enthusiasm and perseverance in learning, and 20% of the students still having low self-confidence.